1998
DOI: 10.1111/j.1939-165x.1998.tb01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis of Feline Platelets in Whole Blood, Including Platelet Count, Mean Platelet Volume, and Activation State

Abstract: A new whole-blood flow cytometric method has been developed for counting and sizing platelets in samples from cats, a species in which platelet and red blood cell sizes overlap significantly. The method is a modified version of the two-angle laser light scattering technology used by Bayer H*System hematology analyzers. The new method provided accurate platelet counts and mean platelet volumes (MPV, fl) for cats. The method also measured mean platelet component concentration (MPC, g/dl), a parameter which was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 22 publications
2
90
2
Order By: Relevance
“…This finding is different from humans, where responses to ADP were lower than responses to COL and AA, and for dogs, where responses to AA appear to have been lower than responses to ADP and COL. 27,33 Furthermore, aggregation responses in our study appear to be lower than responses in dogs and sheep, and only marginally greater than responses in humans, using the same or comparable agonist concentrations. 3,27,32 Cats are considered to have highly aggregable platelets, 35,40 so it was surprising that platelet aggregation responses were not higher compared to other species. Studies in dogs and sheep have demonstrated that aggregation responses can be enhanced by changing agonist concentrations, and similar studies in cats may identify optimal agonist concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is different from humans, where responses to ADP were lower than responses to COL and AA, and for dogs, where responses to AA appear to have been lower than responses to ADP and COL. 27,33 Furthermore, aggregation responses in our study appear to be lower than responses in dogs and sheep, and only marginally greater than responses in humans, using the same or comparable agonist concentrations. 3,27,32 Cats are considered to have highly aggregable platelets, 35,40 so it was surprising that platelet aggregation responses were not higher compared to other species. Studies in dogs and sheep have demonstrated that aggregation responses can be enhanced by changing agonist concentrations, and similar studies in cats may identify optimal agonist concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…d Samples were considered to have undergone aggregation if at any magnification they displayed at least 3 aggregates, each consisting of $3 platelets. 33,37 The percentage of macroplatelets was calculated following the review of 300 consecutive nonaggregated platelets in the monolayer area with the aid of an ocular micrometer at 1,0003 magnification. For the purpose of the current study, spherical platelets with a diameter $5 mm or elongated platelets with a length $5 mm were considered macroplatelets.…”
Section: Smear Evaluationmentioning
confidence: 99%
“…Similar problems with automated analysis are also reported from cats because a significant overlap in size between platelets and red blood cells exists in this species. 15 Interestingly, a recent study demonstrated that a modified flow cytometric method was able to count and size platelets in cats on basis of size and refractive index. 15 That method in addition yielded a new interesting parameter: mean platelet component concentration, which was related to platelet activation state.…”
mentioning
confidence: 99%
“…15 Interestingly, a recent study demonstrated that a modified flow cytometric method was able to count and size platelets in cats on basis of size and refractive index. 15 That method in addition yielded a new interesting parameter: mean platelet component concentration, which was related to platelet activation state. 15 The manual estimation of platelet count from blood smear correlated better with the Unopette platelet count than the automated cell counting systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation